Intersectionality in nursing research: A systematic review - Elin Siira; Karolina Linden; Sara Wallström; Ida Björkman (Wiley, 2023)
Abstract Aim This systematic literature review aimed to identify, appraise and synthesize available research studies that apply intersectionality in nursing research. Design Systematic review. Data Sources Empirical and theoretical nursing studies published before February 2022 were identified from the PubMed and CINAHL databases. Studies were eligible for inclusion if they substantially covered the topics of intersectionality and nursing, had undergone peer‐review, and were written in English. Review Methods The PRISMA 2020 statement for reporting systematic reviews was used to report findings. The Joanna Briggs Institute Critical Appraisal tools were used to assess the quality of the included research studies. Results Out of 331 identified studies, 60 studies were substantially about nursing and intersectionality, and were included in the review. There are a myriad of ways that the concept of intersectionality has been adopted in nursing research. Furthermore, there was great heterogeneity in the definition and application of the concept of intersectionality, and only a few studies were empirical. Conclusion There is a need for robust and clear framing of how the concept of intersectionality is defined and understood in nursing research. There is also a need for more empirical research effectively adopting the concept of intersectionality to enhance our understanding of how health inequities operate within the field of nursing. No Patient or Public Contribution No patients, service users, caregivers or members of the public were involved in this work.